Caribbean Report 12-05-1995 - Orr, Carol (anchor); Michel, Mario (interviewee); Goddard, George (interviewee); Bergeron, Russ (interviewee); Bennett, Neil (interviewee); Brown, Steve (interviewee); Hall, Wes (interviewee) (The British Broadcasting Corporation, 1995)
In Saint Lucia, Opposition Leader Julian Hunte has announced plans to hold an alternative inquiry into the UN funds scandal. Mario Michel, a lawyer comments on how viable this is and what can be achieved from this hearing. George Goddard, Chairman of the Industrial Solidarity Pact warns of more protest actions and describes the effectiveness of the strike in St. Lucia. There is a planned US deportation of former Haitian military leader Emmanuel Constant after he was detained in New York. Russ Bergeron of the Immigration and Naturalization Service described how Mr. Constant was found. Neil Bennett reports on the prosecution of the man accused of murdering Superintendent Jude Matthew, one of the top detectives of St. Kitts. West Indies Manager Wes Hall is confident that the West Indies can overcome their Australian defeat and find victory against England. Speculation continues in two Eastern Caribbean countries, Dominica and Grenada, about possible election dates.
1. Headlines with Carol Orr (00:00-00:30)
2. St. Lucia Opposition mounts an alternative inquiry into the alleged UN funds scandal (00:31-05:52)
3. The former Haitian military leader Emmanuel Constant has been detained in New York, pending a deportation order (05:53-09:41)
4. The prosecution of the man accused of murdering one of the top detectives in St. Kitts begins (09:42-11:23)
Keywords: Political corruption -- Saint Lucia; Strikes and lockouts -- Civil service -- Saint Lucia; Labor unions -- Saint Lucia; Deportation -- United States; United States -- Emigration and immigration -- Government policy; Alien criminals; Cocaine industry -- Saint Kitts and Nevis; Prosecution -- Saint Kitts and Nevis; Drug traffic -- Investigation -- Saint Kitts and Nevis; Cricket -- West Indies; Cricket -- Tournaments -- England; Elections -- Dominica; Elections -- Grenada; Dominica -- Politics and government; Grenada -- Politics and government